2017
DOI: 10.1155/2017/3178263
|View full text |Cite
|
Sign up to set email alerts
|

Colonic Transit Time and Gut Peptides in Adult Patients with Slow and Normal Colonic Transit Constipation

Abstract: Purpose To investigate whether pathophysiological differences exist among healthy controls (HC) and patients with slow and normal transit constipation (STC and NTC), we evaluated (1) gastrointestinal (GI) symptoms using validated questionnaires; (2) circulating concentrations of neurotensin, motilin, corticotrophin-releasing factor (CRF), and somatostatin; and (3) possible differences in frequency distribution of the neurotensin rs1800832 A/G and Neurotensin Receptor 1 rs6090453 C/G SNPs. Methods Fifty-one pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 44 publications
0
14
0
3
Order By: Relevance
“…Overall, STC appears to be caused by impaired colonic motility and a dysfunctional enteric nervous system [20]. A recent study reported that some GI peptides, particularly neurotensin and motilin, are linked to impaired colonic motility in STC constipation [21].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, STC appears to be caused by impaired colonic motility and a dysfunctional enteric nervous system [20]. A recent study reported that some GI peptides, particularly neurotensin and motilin, are linked to impaired colonic motility in STC constipation [21].…”
Section: Discussionmentioning
confidence: 99%
“…Neurotensin acts as a neurotransmitter in the CNS and the ENS [41] and as a hormone peripherally. Through paracrine and endocrine mechanisms, it regulates GI secretion and motility [42]. Additionally, neurotensin plays many roles in GI disorders, and all of its properties still have not been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Colonic motor activity occurs in high-amplitude propagated contractions compartmentalizing colonic segments which eventually results in stool formation [ 41 ]. Gut peptides involved in colonic motility are somatostatin, neurotensins, motilin and corticotrophin-releasing factor (CRF) [ 42 ]. There is no consensus on the golden standard for measuring colonic transit.…”
Section: Gastrointestinal Transit: Methodology and (Patho)physiolomentioning
confidence: 99%